2005
DOI: 10.1016/j.jesp.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

When “different” means “worse”: In-group prototypicality in changing intergroup contexts

Abstract: An experiment with 213 participants provided evidence for in-group projection-the generalization of distinctive in-group attributes to a superordinate category. The frame of reference for in-group (German) judgments was manipulated by presenting either Italians or the British as an out-group. Results showed that attributes on which Germans differed from each out-group were accentuated not only in in-group judgments but also when judging Europeans. By adapting features of the superordinate category to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
117
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 18 publications
18
117
0
Order By: Relevance
“…In line with this speculation, Trafimow and Trafimow (1999) showed that violations of perfect duties (deontological duties) lead to a stronger tendency for person attributions compared to violations of imperfect duties. In intergroup relations, whenever an ingroup and an outgroup are evaluated according to a common standard (e.g., Mummendey & Wenzel, 1999) these standards are conceived of according to ingroup attributes which leads to the perception of outgroups as deviating from this common standard (e.g., Waldzus, Mummendey, & Wenzel, 2005). Here, it is of major importance whether such a common standard is conceived of as a minimal or a maximal standard (Berthold, Mummendey, Kessler, Lücke, & Schubert, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this speculation, Trafimow and Trafimow (1999) showed that violations of perfect duties (deontological duties) lead to a stronger tendency for person attributions compared to violations of imperfect duties. In intergroup relations, whenever an ingroup and an outgroup are evaluated according to a common standard (e.g., Mummendey & Wenzel, 1999) these standards are conceived of according to ingroup attributes which leads to the perception of outgroups as deviating from this common standard (e.g., Waldzus, Mummendey, & Wenzel, 2005). Here, it is of major importance whether such a common standard is conceived of as a minimal or a maximal standard (Berthold, Mummendey, Kessler, Lücke, & Schubert, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification in ingroup projection research is typically measured to check that both groups relevant to participants (e.g., Waldzus, Mummendey, & Wenzel, 2005). Identification with the subgroup may also be an outcome of ingroup projection (Adelman, 2010).…”
Section: Furry Fandommentioning
confidence: 99%
“…The ingroup projection model notes that both the subgroup and superordinate group should be relevant to participants (Waldzus et al, 2003). One way to check the relevance and importance of the groups under investigation is to ensure that the mean rating of identification with both the subgroup and the superordinate group is above the midpoint of the scale (Kessler et al, 2010;Waldzus et al, 2005). Testing this, we found that identification with one's fursona species, t(213) = 13.49, p < .001, d = 1.85, and identification with the furry community, t(213) = 19.71, p < .001, d = 2.70, were both significantly above the midpoint of the scale.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…The third and fourth most cited topics refer to intergroup relations, either focusing on prejudice, racism (e.g. Cabecinhas 2008;Monteiro, França and Rodrigues 2009;Vala, Brito and Lopes 1999;Waldzus, Mummendey and Wenzel 2005) or gender issues (e.g. Amâncio 1994).…”
Section: List Of Most Cited Topics In Social Psychology In Portugalmentioning
confidence: 99%